Design of walking aids for the elderly based on the Kano-AHP-FEC method - Tao Wang; Yanxiao Zhao; Xinda Zhang; Yibao Xie; Leah Ling Li Pang (Scientific Reports)
Abstract As global populations age, ensuring the mobility safety of elderly individuals has become a prominent concern, highlighting the need for innovative designs in assistive products for seniors. This study aims to offer a scientific and practical design methodology for mobility aid designers, validated through the design of a walker for elderly users. To begin, potential user needs for walkers were identified using User Journey Mapping, with these needs categorized through the Kano model to establish a structured hierarchy of design requirements. Then, the Analytic Hierarchy Process was applied to weight these requirements, pinpointing the most critical design needs for walkers to guide practical design decisions. Finally, the Fuzzy Comprehensive Evaluation method was used to systematically assess walker design proposals, helping to identify the optimal solution and specifying areas for improvement. The findings demonstrate that the combined KANO-AHP-FCE framework effectively guides the design of walker products, enhancing their ability to meet user needs. This approach not only provides a valuable reference for future assistive product innovation but also contributes to solutions for enhancing elderly mobility safety in an aging society.